Purification and characterization of thermo alkaliphilic catalase from haloarchaeal strain - Stevens Jones R.D, Murugan S Asha K. R. T (International Journal of Scientific Research and Management (IJSRM), 2017)
In this study, Haloarchaeal strain was isolated from water samples collected from salt pan. The strain was further treated with 2% H2O2 and incubated in a water bath with shaker for 12 days. Supernatant was collected from early log phase and was used as enzyme source. Protein was precipitated by ice cold ethanol followed by purification with Sephadex G-150 column chromatography. SDS-PAGE report showed that that the molecular weight of catalase was found to be 111.2 KD using 12% gel. The results showed that the optimum pH of catalase in supernatant was found to be at 9.0 and optimum temperature was found to be at 65 °C. In case of purified sample the activity of catalase was found to be increased at pH 10 and optimum temperature was noticed at 65ºC. Activity of enzyme was increased in increasing concentration of enzyme upto 2.5ml, beyond that the activity declined. The enzyme has great affinity for the substrate H2O2and the Vmax and Km was calculated as 80mM and 40mM respectively by Michaelis menton plot. The activity of catalase from purified sample was also assayed in the presence of metal ions and the results obtained indicated that the activity was found to be increased significantly from 85.5 mM/mL and the activity was stable and constant up to 171 mM/mL of NaCl and at 0.024mM/mL of MgSO4 and 0.03mM/mL of MnSO4. The activity was found to be decreased when the concentration of ZnSO4 was increased. Keywords: Halobacterium, Catalase, Zobell marine agar, SDS-PAGE